2023
DOI: 10.1101/2023.04.10.536170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-resolved single-cell and spatial gene regulatory atlas of plants under pathogen attack

Abstract: Plant leaf intercellular space provides a nutrient-rich and heterogeneous niche for microbes that critically impacts plant health. However, how individual plant cells respond to heterogeneous microbial colonization remains largely elusive. Here, by time-resolved simultaneous single-cell transcriptome and epigenome profiling of plants (Arabidopsis thaliana) infected by virulent and avirulent bacterial pathogens (Pseudomonas syringae), we present cell atlases with gene regulatory logic involving transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Single-nuclei-based transcriptomics is a powerful technology for elucidating the dynamics of biological processes and understanding the diversity among distinct cell types. The snRNA-seq techniques have enabled researchers to analyze complex traits at a single-cell resolution, particularly emphasizing tissue-specific single-cell atlas, tissue developmental processes, plant-microbe interactions, and abiotic stresses (Kim et al, 2021; Cervantes-Pérez et al, 2022; Tenorio Berrío et al, 2022; Li et al, 2023; Nobori et al, 2023; Sun et al, 2023; Tang et al, 2023). To comprehensively elucidate Si deposition in soybean leaves and its consequential effects on genes specific to individual cells and their associated gene networks, we employed snRNA-seq technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-nuclei-based transcriptomics is a powerful technology for elucidating the dynamics of biological processes and understanding the diversity among distinct cell types. The snRNA-seq techniques have enabled researchers to analyze complex traits at a single-cell resolution, particularly emphasizing tissue-specific single-cell atlas, tissue developmental processes, plant-microbe interactions, and abiotic stresses (Kim et al, 2021; Cervantes-Pérez et al, 2022; Tenorio Berrío et al, 2022; Li et al, 2023; Nobori et al, 2023; Sun et al, 2023; Tang et al, 2023). To comprehensively elucidate Si deposition in soybean leaves and its consequential effects on genes specific to individual cells and their associated gene networks, we employed snRNA-seq technology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have primarily relied on bulk transcriptomics, which fails to report for the cellular heterogeneity and does not consider the specific cell types possessing the ability of nutrient uptake and deposition (Hao et al, 2021). The single nucleus RNA-sequencing (snRNA-seq) has enabled researchers to identify cell-specific gene expression in several organisms (Kim et al, 2021; Cervantes-Pérez et al, 2022; Shahan et al, 2022; Tenorio Berrío et al, 2022; Xia et al, 2022; Nobori et al, 2023; Sun et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This motivated us to comprehensively profile cell identities throughout Arabidopsis development, spanning all major organs present over the plant’s entire life cycle (i.e., from seed to next-generation seeds). Here, we present an initial version of a seed-to-seed atlas of Arabidopsis development that may function as a foundational dataset for more focused studies, as well as be further built upon with future single-cell/nucleus transcriptome and multi-omic studies 19 . Our seed-to-seed single-nucleus transcriptome atlas revealed a vast diversity of previously uncharacterized molecular identities that integrate both cell type and cell state, including both universal and tissue-specific cell type marker genes, which will be a powerful platform for hypothesis generation of specific cell populations along the spatiotemporal axis of Arabidopsis development.…”
Section: Introductionmentioning
confidence: 99%
“…For example epidermal bulliform cells in grasses change their turgor pressure to roll the leaf to slow water loss under stressful conditions, with the TF, ZINC FINGER HOMEODOMAIN 1 (ZHD1), modulating leaf rolling by influencing rice (Oryza sativa) bulliform cell development 14,15 . Several studies have identified CREs functioning in a cell-type-specific manner within various plant species [16][17][18][19][20][21][22][23] . Despite these findings, our understanding of CREs exhibiting evolutionarily conserved or divergent cell-type-specific activities remains limited.Through single-cell assay for transposase accessible chromatin sequencing (scATAC-seq), we constructed an expansive single-cell reference atlas of accessible chromatin regions (ACRs) within rice.…”
mentioning
confidence: 99%